ENGLІSH OAK POPULATІON VARІABІLІTY BY GROWTH AND STEM QUALІTY ІN 30-YEAR-OLD PROVENANCE TRІAL PLANTATІONS - Samoday, V. P. (Forestry and Forest Melioration, 2018)
Introduction Saving and restoring the oak forest stands in conditions of a northern Forest-Steppe is one of the important tasks today. Despite its significant frequency of fruiting, the moving of seed material, and, consequently, the growth of offspring in the new conditions of the plants is not less important question. The aim of the research is to study the variability characteristics of oak-trees and the degree of their inheritance by the progeny depending on the geographic origin of the seed material in the northern Left-bank Forest-Steppe of Ukraine. Materials and Research Methods The research was conducted on the oak-trees created in 1975-1977 in the territory of State Enterprise “Trostyanetske Forest Economy”, the Sumy region. The total area of cultures amounted to17.5 hectares. There were 27 oak ecotypes representing the population of oak from all parts of the area of the European part of the former USSR . The placement of the seats is 2.5 ? 0.7 m. The research was carried out according to conventional plant breeding and forest inventory methods. To analyze the provenance growth, the comparison was performed using indices of the local origin oak. The data field analysis is carried out using methods of forest statistics, Student's t-test and the single ANOVA factor (analysis of variance). Results It was determined that, in the Left-bank Forest-Steppe of Ukraine, the 30-years-old provenances from Transcarpathian (t = 4.04), Voronezh (t = 3.05) and Rivne (t = 2.01) regions have significantly better average height indices while the provenances from Volgograd region (t = -4.57) and the Republic of Bashkortostan (t = -4.21) have significantly worse ones. By the indices of average diameter, the progenies of the eastern population were significantly higher than the oak of local origin – provenance from the Volgograd region (t = 3.71), Rivne, Transcarpathian and Mohilev regions (t = 2.26). The provenances from Mohilev, Transcarpathian and Belgorod regions which exceed the stock volume of homegrown oak by 30-50 % were the most productive in the trials. The variations from the Volgograd Region and the Republic of Bashkortostan were revealed as low productive in test. Analysis of the qualitative structure of population progenies indicates the high stem quality for provenances of western Ukrainian origin and for the most of provenances from Central Black Earth region of Russia and Belarus, the percentage of strong stems of which is ranged from 60 % to 90 %. The provenances from the east (the Volgograd Region and the Republic of Bashkortostan) and south (the Luhansk and Kirovohrad regions and the Crimea) were revealed as low quality in provenance trial. Percent of strong trunks in the provenance trials ranges from 15 % to 40 %. Conclusions The results of the studies found that according to the quantitative and qualitative characteristics in geographical cultures of oak, the plants from Grodno, Bryansk and Rivne region were the best, the worst ones were the oak trees from Volgograd region, Republic of Bashkortostan and Crimea. To reproduce oak stands in conditions of Left-bank Forest-Steppe of Ukraine the most promising is the movement of seed material from the western, northern and north-eastern spreading areas of oak. Undesirable is the delivery of seeds from the eastern and southern directions. These findings are preliminary, despite the age of the cultures, and can be revised during the further growth of the research collection.